Diagnostic Accuracy of Immunologic Biomarkers for Accurate Diagnosis of Bloodstream Infection in Patients with Malignancy: Procalcitonin in Comparison with C-Reactive Protein - Mansoureh Shokripour; Navid Omidifar; Kourosh Salami; Mohsen Moghadami; Babak Samizadeh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Purpose. To calculate the diagnostic value of C-reactive protein (CRP) and serum procalcitonin (PCT) levels for the pathologic presence of microbes in the bloodstream of patients with malignancy, in comparison with blood culture. Methodology. Blood culture (by reference method) and assay results of PCT and CRP of febrile patients, with clinical suspicion to blood infections, were collected. Statistical aspects of PCT  and CRP tests were evaluated. Results. Data from 255 cases were gathered. The area under the curve for differentiating bacteremia from nonbacteremia for PCT (0.741) was superior to that of CRP (0.612). Amongst the different cutoffs of PCT and CRP, the cutoff of ≥1.17 ng/ml and >47 mg/l had the sensitivity of 75 and 58.3%, the best NPV of 91.5% and 81.3%, and the best specificity of 79.9% and 72.8%, respectively. Discussion. Despite statistically nonsignificant results, PCT seems to be a superior indicator to CRP for rejecting the presence of microorganism in bloodstream. For PCT, the cutoff value of 1.17 ng/ml (bacteremia from nonbacteremia) had the highest NPV value of 91.5% in malignant patients, suspicion of sepsis.